ANALISIS MAKNA OBJEK TEMPAT DUDUK DALAM ANIMASI “LA DIPLOMATIE DE L’ECLIPSE” (2022) - Lawrence, Kezia; Grahita, Banung (VCoDe : Visual Communication Design Journal, 2024)
La Diplomatie De L'eclipse (2022) is a short animation work done by five students from Ecole MoPA. In this animation, it was found that objects in the form of "seats" are often shown significantly in numerous scenes. Objects or properties themselves can have a supporting function in conveying the narrative in films. This research aims to examine the narrative function of "seats" in this animation using Roland Barthes' semiotic theory. The results show that visual signs in the form of character interactions with said objects function as a reflection of character development, relationships between characters, and the overall message of the story.